Spillover effects of the European Central Bank's Expanded Asset Purchase Program to non-eurozone countries in Central and Eastern Europe - Mark Antal; Lorant Kaszab (Magyar Nemzeti Bank, 2021)
For a panel of six Central and Eastern European countries outside the eurozone (Bulgaria, Croatia, Czechia, Hungary, Poland and Romania) we estimate the spillover effects of the European Central Bank's Expanded Asset Purchase Program (APP) on exchange rates, equity prices, government bond yields of various maturities, and CDS spreads. We find that the most pronounced spillovers induced sovereign bond yields to drop by around 1-6 basis points in a two-day time window in response to the Public Sector Purchase Program (PSPP) announcements.
Keywords: E51; E32; E44; F45; F47; 330; ordinary least squares estimation; panel data; unconventional monetary policy